Chemcalc: online chemistry calculator / Nur Atiqah Zaharullil, Muhammad Afifi Muhammad Sabri and Nurul Husaifah Mohd Hanapi - Zaharullil, Nur Atiqah; Muhammad Sabri, Muhammad Afifi; Mohd Hanapi, Nurul Husaifah (Universiti Teknologi MARA, Kedah, 2023)
A calculator is a device that facilitates rapid and easy mathematical operations on numerical data. Online chemical calculators are essential tools for students, scientists to solve difficult equations. Using an interactive software application that performs a predetermined set of mathematical operations, it might provide any mathematical operation, including unit conversions, pH calculations, and calculations of chemical reactions. The benefits of using an online calculator include accurate, efficient, rapid, and practical online computations in a range of sectors. Nowadays, with the advancement of technology, it is crucial for students to get used to an online calculator, as it provides several advantages like greater convenience, accessibility, and usability. Students studying chemistry in particular encounter challenges as they need to memorize numerous mathematical formulas to solve the chemistry problems. Therefore, the development of an online calculator for chemistry subjects provides the students with the best opportunity to succeed in chemistry class without having to memorize every formula. Numerous mathematical algorithms, including unit conversion, mole conversion, pH calculation, titration, dilution, concentration, and many others, are available in this online chemistry calculator. A total of 124 Basic Chemistry students were introduced to the online calculator. Students were given a set of chemistry questions, and they had to use an online calculator to solve a set of chemistry problems that were provided to them. Many students said it was incredibly convenient to use this online calculator on their tablet or smartphone. They further asserted that using this online calculator would allow them to finish the questions more quickly.